2022
DOI: 10.1001/jamanetworkopen.2022.25657
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization in the 6 Months Following SARS-CoV-2 Infection

Abstract: Key Points Question Is SARS-CoV-2 associated with health care utilization 6 months after the acute stage of infection? Findings In this cohort study of 127 859 patients with positive SARS-CoV-2 test results matched to 127 859 patients with negative SARS-CoV-2 test results, health care utilization was elevated in patients with positive SARS-CoV-2 results 6 months after the acute infection. Other than COVID-19 and infectious disease sequelae, the most notable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 37 publications
1
33
2
Order By: Relevance
“…Individual conditions within each category were also evaluated. Because of the limited clinical and epidemiologic relevance [ 16 ], we did not look at dementia/cognitive impairment outcomes in individuals <18 years. Outcomes could be ascertained at any time after the acute phase of infection (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Individual conditions within each category were also evaluated. Because of the limited clinical and epidemiologic relevance [ 16 ], we did not look at dementia/cognitive impairment outcomes in individuals <18 years. Outcomes could be ascertained at any time after the acute phase of infection (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Individual conditions within each category were also evaluated. Because of the limited clinical and epidemiologic relevance, [16] we did not look at dementia/cognitive impairment outcomes in individuals <18 years. Outcomes could be ascertained at any time after the acute phase of infection (i.e., immediately after discharge in hospitalized patients and ≥4 weeks in outpatients) and no minimum follow-up time was required.…”
Section: Study Eligibilitymentioning
confidence: 99%
“… 13 , 28 Tartof et al found COVID-19-associated excess health care utilization in the six months following SARS-CoV-2 infection, but their study did not look at utilization by disability status. 29 Adults with disabilities have more underlying chronic conditions, social vulnerability factors 6 , and pandemic-related behavioral or mental health changes 12 , 7 than adults without disabilities, and associated increased care needs and expenditures for social services. 9 They experience greater challenges than adults without disabilities in accessing health care services 30 (e.g., testing, vaccination, nonpharmaceutical interventions, clinic visits) and might be at higher risk for undiagnosed SARS-CoV-2, leading to missed cases, 13 e.g., PCC in adults with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%